2022
DOI: 10.1177/10406387211069552
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of respiratory coinfections in pig herds with enzootic pneumonia: a survey in Brazil

Abstract: Mycoplasma hyopneumoniae is the primary etiologic agent of swine enzootic pneumonia (EP), in which the immune response is reduced, making pigs susceptible to secondary infections. We surveyed commercial pig herds in Brazil for viral and bacterial respiratory coinfections that could complicate EP. Over a 2-y period (2015–2016), we found that 854 of 2,206 pigs (38.7%) were positive for M. hyopneumoniae in herds from various production systems in 3 Brazilian regions (Central-West, Southeast, South). We collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Additionally, infectious agents frequently associated with PRD in pigs from Brazil include IVA, PCV2, Mycoplasmopsis hyopneumoniae [ 49 , 50 , 51 , 63 ], Pasteurella multocida [ 49 , 51 ], Glaesserella parasuis , formerly known as Haemophilus parasuis [ 49 , 63 ], and Actinobacillus pleuropneumoniae [ 63 ]. The non-detection of IVA and PCV2 using specific qPCR assays for these pathogens suggested that these viral agents were not associated with the development of the interstitial pneumonia observed in the wild boars during this investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, infectious agents frequently associated with PRD in pigs from Brazil include IVA, PCV2, Mycoplasmopsis hyopneumoniae [ 49 , 50 , 51 , 63 ], Pasteurella multocida [ 49 , 51 ], Glaesserella parasuis , formerly known as Haemophilus parasuis [ 49 , 63 ], and Actinobacillus pleuropneumoniae [ 63 ]. The non-detection of IVA and PCV2 using specific qPCR assays for these pathogens suggested that these viral agents were not associated with the development of the interstitial pneumonia observed in the wild boars during this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The bronchointerstitial pneumonia identified during this study is characteristic of Mycoplasmopsis spp.-induced infections in pigs [ 53 , 54 ], and is consistent with previous studies done in Brazil [ 49 , 50 , 51 ]. Investigations of the etiologic agent associated with pulmonary disease in pigs from different geographical regions of Brazil confirmed that bronchointerstitial pneumonia is frequently associated with infections due to M. hyopneumoniae [ 49 , 50 , 51 , 63 , 67 ]. Therefore, it was rather likely that these wild boars were infected by M. hyopneumoniae .…”
Section: Discussionmentioning
confidence: 99%
“…The DNA was extracted from PUCS using commercial kits (NewGenePrepAmp, Simbios Biotecnologia, Cachoeirinha, Brazil). The PCV-2 quantitative real-time PCR (qPCR) was performed using the NewGene PCVAmp kit (Simbios Biotecnologia, Cachoeirinha, Brazil) and specific primers ( 28 ). The standard curve was generated using references with high (10,000,000 genomes/mL), low (10,000 genomes/mL), and intermediate (10,000–1,000,000 genomes/mL) load, considering a linear regression coefficient ( R 2 ) above 0.9.…”
Section: Methodsmentioning
confidence: 99%
“…The possible limitations of our study relate to the putative presence of other important infectious agents in pig farming, such as Mycoplasma hyopneumoniae, a causative agent of porcine respiratory disease complex frequently reported in Southeast Brazil in combination with other bacterial or viral agents (Balestrin et al, 2022), which were not investigated. Additionally, the crosssectional design of the investigation did not allow observation of the dynamics of infections and their associations with the lesions observed in the tissues.…”
Section: /9mentioning
confidence: 99%